2020
DOI: 10.1055/s-0040-1715090
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Venous Thromboembolism following Knee Arthroscopy: Effectiveness of a Risk-Based Stratified Chemoprophylaxis Protocol

Abstract: The incidence of symptomatic venous thromboembolism (VTE) has been reported in up to 10.9% of patients undergoing knee arthroscopy without chemoprohylaxis. The purpose of this study was to evaluate the effectiveness of a chemoprophylaxis protocol in patients undergoing knee arthroscopy. A retrospective review of prospectively enrolled patients in a new institutional VTE prophylaxis protocol identified all patients undergoing knee arthroscopy during a 5-year period. This risk-based chemoprophylaxis protocol was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…DVT after knee arthroscopy is documented in the literature at a rate of 2.0% of patients within 2 months after surgery, with the highest rates among ACL procedures. 29 This study found a DVT rate of 0.98% at 3 months after surgery, which was similar to previous studies. Comparatively, hip arthroscopy DVT incident rates have been reported at 0.76% and 1.4%, 1 , 13 while our study reported a rate of 0.66% at 3 months after surgery.…”
Section: Discussionsupporting
confidence: 92%
“…DVT after knee arthroscopy is documented in the literature at a rate of 2.0% of patients within 2 months after surgery, with the highest rates among ACL procedures. 29 This study found a DVT rate of 0.98% at 3 months after surgery, which was similar to previous studies. Comparatively, hip arthroscopy DVT incident rates have been reported at 0.76% and 1.4%, 1 , 13 while our study reported a rate of 0.66% at 3 months after surgery.…”
Section: Discussionsupporting
confidence: 92%
“…Rationale: Patients undergoing orthopaedic surgery are at risk of VTE 2214-2221 . Rehabilitation including early ambulation is of utmost importance to prevent VTE 2222,2223 .…”
Section: - Should the Post-operative Rehabilitation Of Patients Who H...mentioning
confidence: 99%
“…Consensus also could not be achieved for arguably the commonest knee arthroscopic surgery that is routinely performed, namely ACL reconstruction. There is published evidence that ACL reconstruction is associated with the maximum incidence of VTE following knee arthroscopy, followed closely by meniscal repair [ 33 ]. The panel could not reach consensus for meniscal repair as well, but through their comments indicated that VTE for single ligament reconstructions and meniscal repair is merited based solely upon patient factors.…”
Section: Discussionmentioning
confidence: 99%